Tedaniophorbasins A and B—Novel Fluorescent Pteridine Alkaloids Incorporating a Thiomorpholine from the Sponge Tedaniophorbas ceratosis - Asadhawut Hiranrat; Darren C. Holland; Wilawan Mahabusarakam; John N. A. Hooper; Vicky M. Avery; Anthony R. Carroll (Marine Drugs, 2021)
Two new fluorescent pteridine alkaloids, tedaniophorbasins A (1) and B (2), together with the known alkaloid N-methyltryptamine, were isolated, through application of mass directed purification, from the sponge Tedaniophorbas ceratosis collected from northern New South Wales, Australia. The structures of tedaniophorbasins A and B were deduced from the analysis of 1D/2D NMR and MS data and through application of 13C NMR DFT calculations. Tedaniophorbasin A possesses a novel 2-imino-1,3-dimethyl-2,3,7,8-tetrahydro-1H-[1,4]thiazino[3,2-g]pteridin-4(6H)-one skeleton, while tedaniophorbasin B is its 2-oxo derivative. The compounds show significant Stokes shifts (~14,000 cm−1) between excitation and emission wavelengths in their fluorescence spectra. The new compounds were tested for bioactivity against chloroquine-sensitive and chloroquine-resistant strains of the malaria parasite Plasmodium falciparum, breast and pancreatic cancer cell lines, and the protozoan parasite Trypanosoma brucei brucei but were inactive against all targets at 40 µM.